Health-Related Quality of Life (HRQoL) among Elderly Turkish and Polish Migrants and German Natives : The Role of Age, Gender, Income, Discrimination and Social Support - Johanna Buchcik; Joachim Westenhöfer; Mick Fleming; Colin R. Martin (People's Movements in the 21st Century - Risks, Challenges and Benefits, 2017)
Background: Migration can negatively and positively influence health-related quality of life (HRQoL). Yet, little is known about the HRQoL of Turkish and Polish migrants and German natives.